Development of Interactive Multimedia Learning Based on Educational Games in Basic Chemistry Learning Media - Oktadio, Albynola Agis; Pardede, Andrew Naftali (Universitas Amikom Purwokerto, 2024)
The purpose of this study is to investigate the features and efficacy of educational game-based MPI for high school colloid system learning. The stages of problem and potential identification, data collection, product design, design validation, product revision, product testing, design revision, use testing, and product revision were all included in the Research and Development (R&D) research method's design in order to produce a final product. Following the development process, learning media with the following qualities were created as the end product: 1) interactive; 2) engaging and enjoyable; 3) serving as a general and autonomous learning medium on high school curriculum; and 4) practical and compatible. All of the criteria—students who completed KSM 70, which represents no less than 70% of the total student body, students who exhibited very good interests, and students who exhibited very high activity, which represents no less than 70% of the total student body—were found to be effective in the trial use. With a completeness of 92.44%, very good interest of 87.33%, and very high activity of 88.11%, it can be concluded from the research and discussion results that MPI based on education games is effectively implemented in chemistry learning in class XI colloidal systems material at SMA Level.